Physical activity and exercise intensity terminology: A joint American College of Sports Medicine (ACSM) expert statement and Exercise and Sport Science Australia (ESSA) consensus statement - Bishop, D. J.; Beck, B.; Biddle, S. J. H.; Denay, K. L.; Ferri, A.; Gibala, M. J.; Headley, S.; Jones, A. M.; Jung, M.; Lee, M. J.-C.; Moholdt, T.; Newton, R. U.; et al. (Medicine & Science in Sports & Exercise, 2025)
The evidence supporting the many beneficial effects of physical activity, including exercise, is overwhelming. This has led to numerous publications, statements, and position stands providing evidence-based recommendations to realize the performance-enhancing and therapeutic benefits of exercise. However, one factor hampering research and limiting the adoption of these recommendations is the inconsistent use of terminology associated with different exercise intensities. The goal of this international group of researchers and practitioners, therefore, was to propose standardized physical activity and exercise intensity terminology that has utility across all ages, sexes, genders, physical abilities, conditions, applications, and activities. After much discussion, we propose a standard terminology for physical activity, exercise, and sport and human performance comprising five exercise intensities: very low, low, moderate, high, and very high. We also propose five different descriptors for the perception of effort that align with the five intensities we have suggested: very easy, easy, somewhat hard, hard, and very hard. To enable consistent use of these descriptors with both cardiorespiratory and resistance exercise, we suggest not using descriptors such as light, heavy, weak, or strong (which might be perceived as only being applicable to describing load). We appreciate that some fields have long-established terminology and may be reluctant to change. Nonetheless, at a minimum, the terminology proposed here allows for more clarity when comparing the different exercise intensity descriptors currently used by different fields. Finally, we hope this will be an important "first step" in harmonizing the descriptions of exercise intensity across the fields of physical activity for public health, exercise science, and sport science.